When cultures collide : leading across cultures : a major new edition of the global guide. - Lewis, Richard Donald, 1930- (Boston : Nicholas Brealey International, 2009)
Capturing the rising influence of culture and the seismic changes throughout many regions of the world, cross-cultural expert and international businessman Richard Lewis has significantly broadened the scope of his seminal work on global business and communication. Now covering more than 60 countries and every major region in the world, this thoroughly updated and expanded third edition of When Cultures Collide continues to break new ground. New chapters on more than a dozen countries - from Iraq, Israel and Pakistan to Serbia, Colombia and Venezuela - vastly broaden the range. Building on his powerful LMR model, Lewis gives leaders and managers practical strategies to embrace differences and work successfully across increasingly diverse business cultures.
Inhoudsopgave : 1. Getting to grips with cultural diversity 2. Managing and leading in different cultures 3. Getting to know each other
Keywords: Cultuur en maatschappij; Cultuur; Cultuurverschillen; Diversiteit; Interculturele communicatie; Internationale bedrijven -- Management -- Sociale aspecten; Management -- Sociale aspecten; Management; Wereldeconomie